Equilibrium Behaviour of Creative Accounting Practices for Financing Externally Evidence from Turkey - Ponce, Herenia Gutiérrez; Chamizo González , Julián; Al-Mohareb, Manar (The journal of contemporary issues in business and government, 2021)
This paper examines the impact of using creative accounting practices on external financing processes and the priorities available to Turkish manufacturing firms in achieving equilibrium reporting strategies for external financing at the lowest possible cost. Following a literature review, creative accounting practices are measured to demonstrate steady earnings streams as an income smoothing strategy in Big Bath theory’s scope using unexpected accruals to justify external financing. Since the management can maintain its presence at the lowest costs resulting from economic fluctuations in the Turkish market, the firm priorities for external financing are determined rationally to fund capital expenditures or finance operations sustainably without depleting financial resources by adopting equilibrium reporting strategies represented by the creative accounting practices. The paper data are collected from 143 Turkish manufacturing firms listed in the Istanbul Stock Exchange using the Orbis database in 2015-2019. Multiple regression is used to test hypotheses. The study concluded that unexpected accruals are significantly related to external financing to achieve sustainable growth, but it is not strong enough. Some determinants have a positive moderating effect on the negative relationship between earnings management and external financing needs. This paper provides new insights into the Turkish market regarding managers priorities for creative accounting practices. It gives broader horizons to research some of the determinants that may affect the relationship between creative accounting practices and external financing.